Effectiveness of introduction of specialised female surgical clinic in a tertiary care hospital - Singh, Atul Kumar; Sharma, Anshuman; Pandey, Shailja; Jain, Siddharth; Sharma, Vishal; Aggarwal, Shubhangi (International Surgery Journal, 2019)
Background: Specialised female surgical clinics are the need of the day and not addressed routinely in the Surgical Department. The management of surgical problems in female patients requires multidisciplinary approach mainly general surgery, obstetrics and gynaecology, general medicine, paediatrics, dermatology and psychiatry. The aim and objective was to introduce a new concept of subspecialty and super speciality in management of female surgical diseases. Methods: Prospective educational interventional study. 18 out of 60 sensitised interns were introduced and oriented in the specialised female surgical clinic. A total of 952 patients visiting the Clinic were studied. Statistical analysis was done. Results: Feedback of female patients were taken and recorded in a proformas and their analysis was done. There was a significant improvement in the knowledge and skill of the participating interns. 99.2% (944 cases) of the female patients were willing to continue their visit to such a specialized clinic in future. Conclusions: It can be concluded that there is a requirement and need of a fully functional specialized female surgical Clinic in our hospital.